Formulation of Liquid Membrane for Silver Extraction - Mohd Adnan, Raudah; Azman, Nurain Syafina; Abd Rahman, Nur Syamimi; Azhan, Siti Nuraina; Abu Bakar Sidik, Dilaeleyana; Othman, Norasikin; Jusoh, Norela (Multidisciplinary Applied Research and Innovation, 2021)
Liquid membrane technology has been an uprising method in the removal of heavy metals. Recovery of heavy metals especially from wastewater is vital to ensure the wellness of public health and environment. Silver is one of the heavy metal that is identified to have harmful toxic properties. In this study, an emulsion liquid membrane is formulated by choosing the best formulation to extract silver from wastewater. An emulsion liquid membrane consists of a combination of potential carrier, diluent and stripping agent. Two different types of substances for each component are compared in this study by screening process to determine its extraction yield for silver. 0.2M tridodecylamine (TDA) and tricotylamine (TOA) as carrier, kerosene and palm cooking oil as diluent and 0.1M sodium hydroxide and hydrochloric acid as stripping agent were used as a component in this study. Meanwhile, 30 ppm silver nitrate solution is used to act as substitute for silver contaminated wastewater. Results show that TDA and palm oil gives the highest extraction yield which are 67.18% and 94.10% respectively. As for the stripping agent, sodium hydroxide and hydrochloric acid were achieved 82.8 % and 81.28 % of extraction rate. Thus, an emulsion liquid membrane consists of 0.2M tridodecylamine, cooking palm oil and 0.1M sodium hydroxide exhibits good performance on removal of silver from wastewater.